2018
DOI: 10.21577/0103-5053.20180081
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Newly Fused 1,2-Dihydropyrido[3,4-b], Bridged Oxadiazol-2-yl, 4-Substituted-benzylidene Hydrazide and Arylidene 6-Chloroquinoxaline 1,4-Dioxides

Abstract: Some simple reactions using commercially available chemicals were used in the preparation of new biologically remarkable quinoxaline 1,4-dioxide derivatives. Several steps performed on 4-chloro-2-nitroaniline resulted in a quinoxaline 1,4-dioxide derivative, which reacted with dimethylformamide dimethylacetal (DMF-DMA) to produce an enamine. Transamination of this enamine with anilines gave the fused 1,2-dihydropyrido[3,4-b]quinoxaline 5,10-dioxide derivatives via an addition-elimination mechanism. Basic conde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Similarly, enamine 34 was obtained from 2-carboethoxy-7-chloro-3-methylquinoxaline 1,4-dioxide and DMADMF [ 82 ]. The transamination of this derivative with morpholine gives enamine 35 , while the reaction with anilines is accompanied by cyclization to pyridin-2-ones, leading to the formation of derivatives 36a – c in good yields ( Scheme 11 ).…”
Section: Chemical Properties Of Quinoxaline 14-dioxidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, enamine 34 was obtained from 2-carboethoxy-7-chloro-3-methylquinoxaline 1,4-dioxide and DMADMF [ 82 ]. The transamination of this derivative with morpholine gives enamine 35 , while the reaction with anilines is accompanied by cyclization to pyridin-2-ones, leading to the formation of derivatives 36a – c in good yields ( Scheme 11 ).…”
Section: Chemical Properties Of Quinoxaline 14-dioxidesmentioning
confidence: 99%
“…Azide 73 rearranges into 2-alkyl carbamates 74a-c or substituted ureas 75a-c when boiled in an alcohol or amine solution, respectively (Scheme 33) [120]. The transformations of the hydrazide of 3-methylquinoxaline-2-carboxylic acid 76, obtained from the corresponding ethyl ester and hydrazine, are applied to the functionalization of the quinoxaline 1,4-dioxide scaffold at position 2 [82]. Condensation of hydrazide 76 with benzaldehydes in the presence of acetic acid in ethanol gave hydrazones 77a and 77b (Scheme 34).…”
Section: Transformations Of Carboxylic Acids and Their Derivativesmentioning
confidence: 99%
“…In addition, a phase II clinical trial for the anticancer drug Tirapazamine (3‐amino‐1,2,4‐benzotriazine‐1,4 dioxide) was recently accomplished (Covens et al, 2006; Maluf et al, 2006). Even though QdNOs are still in the research stage, they have been shown to have a lot of therapeutic potential (Said et al, 2018).…”
Section: Introductionmentioning
confidence: 99%